Perovskite solar cell with passivated bottom

By using the bottom nanocrystal mixed passivation method of combining nano-oxide particles and organic passivation molecules in perovskite solar cells, the problem of peeling off the perovskite layer and substrate is solved, and the photoelectric conversion efficiency and stability are improved.

CN119546033AActive Publication Date: 2025-02-28NANJING UNIV

Patent Information

Application Number
CN202411564810.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-28
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

During the large-area preparation of perovskite solar cells, problems such as insufficient interface adhesion, accumulation of internal stress, mechanical damage and film material defects lead to peeling of perovskite layer and substrate, affecting device performance and stability.

Method used

A nanocrystal mixed passivation method is used to combine nano-oxide particles and organic passivation molecules. By adjusting the mass ratio of insulating oxides and organic passivation molecules, a nanocrystal mixed passivation layer is prepared to enhance interface adhesion and mechanical strength and reduce internal stress.

Benefits of technology

It effectively relieves the internal stress at the bottom, enhances mechanical adhesion, avoids the occurrence of peeling, and improves the photoelectric conversion efficiency. Specifically, the photoelectric conversion efficiency of small-area perovskite solar cells has increased from 23.02% to 25.48%, and large-area modules have also achieved a photoelectric conversion efficiency of 20.28%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546033A_ABST
    Figure CN119546033A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell with a passivated bottom. The perovskite solar cell sequentially comprises a transparent conductive substrate, a hole transport layer, a nanocrystalline mixed passivation layer, a perovskite light absorption layer, an electron transport layer and a back electrode from a light receiving front surface to a light receiving back surface, the nanocrystalline mixed passivation layer is made of insulating oxide and organic passivation molecules. According to the bottom nanocrystal passivation method, the nanometer oxide particles and the organic passivation molecules are combined and mixed to form the bottom nanocrystal, the passivation adsorption effect of the bottom can be enhanced, the passivation area is increased, more binding sites are provided, the internal stress of the bottom is effectively relieved, the mechanical adhesive force is enhanced, the stripping phenomenon is avoided, and the photoelectric conversion efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a bottom-passivated perovskite solar cell. Background Art

[0002] As a kind of renewable energy, solar energy is an inexhaustible, environmentally friendly and ideal energy source, with a potential annual power generation of up to 23,000 TW. Solar cells use the photovoltaic effect to directly convert solar energy into electrical energy, which has attracted great attention from the energy industry to meet the growing demand for sustainable green and clean energy. Crystalline silicon solar cells are now widely used in the market, but after decades of technological research and industrial development, their performance has been continuously improved and basically reached its peak, with very little room for improvement. Their purity must reach more than 99.9999% to be used in solar cell manufacturing, which is expensive. The record power conversion efficiency (PCE) of perovskite solar cells (PSCs) has increased from 3.8% in the past to more than 26% at present, which is comparable to commercial silicon solar cells. Most importantly, PSCs have great advantages in easy manufacturing and solution-based processing costs. Therefore, it is of great significance to further study perovskite solar cells and promote their industrial applications.

[0003] However, in the process of industrial application of perovskite solar cells, in order to improve its production efficiency and reduce the production cost per unit area, it is very necessary to prepare PSC on a large area. However, in the process of enlarging the area of ​​perovskite materials, due to insufficient interface adhesion, internal stress accumulation, mechanical damage, the number of film material defects and other reasons, the peeling phenomenon of the perovskite layer and the substrate is a common problem, which may seriously affect the performance and stability of the device. In order to meet these challenges, it is necessary to optimize the substrate surface treatment process, enhance the interface adhesion, reduce the accumulation of internal stress, and improve the mechanical strength of the bottom layer. In addition, although the passivation technology on the surface of perovskite films has become more and more mature, the directional passivation at the bottom of the perovskite film still faces many process difficulties in actual operation. For example, when the passivation molecules are simply coated on the substrate, these molecules are easily dissolved during the preparation of the perovskite solution and cannot be effectively anchored to the lower interface. Further problems include that due to factors such as weak interface adhesion, insufficient chemical bonding force and mismatch of interface roughness, the passivation molecules may fall off from the interface and mix into the perovskite layer, destroying its internal structure, thereby reducing the overall performance of the PSC component.

[0004] To address these issues, developing new interface engineering technologies and materials to enhance the passivation effect and improve the mechanical strength of the interface is the key to improving the performance and stability of large-area PSCs. Summary of the invention

[0005] The object of the present invention is to provide a bottom-passivated perovskite solar cell, which comprises, from the light-receiving front side to the light-receiving back side, a transparent conductive substrate, a hole transport layer, a nanocrystalline mixed passivation layer, a perovskite light-absorbing layer, an electron transport layer and a back electrode; The bottom nanocrystalline mixed passivation layer is made of insulating oxide and organic passivation molecules, and the mass ratio of the insulating oxide to the organic passivation molecules is 3:1-1:3.

[0006] Furthermore, the insulating oxide is silicon oxide, aluminum oxide or zirconium oxide, and the particle size of the insulating oxide is 5-100 nm.

[0007] Furthermore, the organic passivation molecule is phenethylammonium iodide (PEAI), 4-fluorophenethylammonium iodide (4F-PEAI), 4-fluorophenethylammonium chloride (4F-PEACl), phenethylammonium chloride (PEACl), 4-trifluoromethylphenylammonium chloride (CF3-PACl), ethylenediamine iodide (EDADI), trioctylphosphine oxide (TOPO), 1-octadecanethiol (ODT) or triphenylphosphine (PPh3).

[0008] In one embodiment of the present invention, the bottom nanocrystalline mixed passivation layer is made of nano-silicon dioxide and 4-fluorophenethylammonium chloride (4F-PEACl), and the mass ratio of nano-silicon dioxide to 4-fluorophenethylammonium chloride (4F-PEACl) is 1:1.

[0009] Furthermore, the transparent conductive substrate is an indium tin oxide (ITO) substrate, an indium tungsten oxide (IWO) substrate, a fluorine-doped tin oxide (FTO) substrate, an indium zinc oxide (IZO) substrate or an aluminum-doped zinc oxide (AZO) substrate.

[0010] Furthermore, the hole transport layer is made of a p-type semiconductor material selected from nickel oxide (NiO x ), molybdenum oxide (MoO3), cuprous oxide (Cu2O), cuprous iodide (CuI), copper phthalocyanine (CuPc), cuprous thiocyanate (CuSCN), redox graphene, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA, poly (triaryl amine)), 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (Spiro-OMeTAD), poly 3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT:PSS), poly [bis (4-phenyl) (4-butylphenyl) amine] (Ploy-TPD), monolayer, etc. One or more.

[0011] Furthermore, the perovskite light absorbing layer is made of a perovskite material ABX3, wherein: A is selected from the group consisting of formamidinium ions (FA +), methylamine ion (MA + ), cesium ion (Cs + ); B is selected from lead ions (Pb 2+ ), tin ions (Sn 2+ ), Germanium ions (Ge 2+ ); X is selected from iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ).

[0012] Furthermore, the electron transport layer is made of n-type semiconductor material, selected from fullerene (C 60 ), graphene, fullerene derivatives [6,6]-phenyl-C 61 -methyl butyrate (PCBM), carbon nanotubes, etc., or one or more thereof.

[0013] Furthermore, the back electrode may be a metal electrode or a metal grid electrode. The metal grid electrode may be made of one or a combination of metal materials such as gold, palladium, silver, titanium, chromium, nickel, aluminum, copper, etc.; the grid electrode may be prepared by vacuum evaporation, sputtering, atomic layer deposition, 3D printing, screen printing, inkjet printing, etc.

[0014] The second object of the present invention is to provide a method for preparing the bottom passivated perovskite solar cell. providing a transparent conductive substrate; forming a hole transport layer on the upper surface of the transparent conductive substrate; forming a nanocrystalline hybrid passivation layer on the upper surface of the hole transport layer; forming a perovskite light absorbing layer on the upper surface of the bottom nanocrystalline hybrid passivation layer; forming an electron transport layer on the upper surface of the perovskite light absorbing layer; A back electrode is formed on the upper surface of the electron transport layer.

[0015] Furthermore, the nanocrystalline mixed passivation layer is formed on the upper surface of the hole transport layer by dissolving the insulating oxide and the organic passivation molecules in a solvent and then coating them on the hole transport layer by a scraping method.

[0016] A third object of the present invention is to provide a photovoltaic module comprising at least one cell string, wherein the cell string comprises at least two of the above-mentioned perovskite solar cells.

[0017] The present invention adopts the combination of nano-oxide particles and organic passivation molecules. The bottom nanocrystal passivation method formed by the mixture of the two can enhance the passivation adsorption effect of the bottom, increase the passivation area, provide more binding sites, effectively relieve the bottom internal stress, enhance the mechanical adhesion, avoid the occurrence of peeling, and improve the photoelectric conversion efficiency. 2 In the preparation of perovskite solar cells with an effective area, the photoelectric conversion efficiency was increased from 23.02% to 25.48%. In addition, when this method was applied to the preparation of large-area components, a photoelectric conversion efficiency of 20.28% was obtained on an effective area of ​​20.25 cm². BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the device structure after introducing a bottom nanocrystal hybrid passivation layer into a perovskite solar cell.

[0019] Figure 2 Time-of-flight secondary ion mass spectrometry of perovskite films with and without bottom nanocrystal hybrid passivation.

[0020] Figure 3 X-ray diffraction patterns of perovskite films with and without bottom nanocrystal hybrid passivation at different incident angles.

[0021] Figure 4 The Fourier infrared spectra of the passivation layer when only passivation molecules, only oxide nanocrystals, and a mixture of the two are used.

[0022] Figure 5 The fluorescence spectra of perovskite films without passivation layer, using only passivation molecules, using only oxide nanocrystals, and a mixture of the two.

[0023] Figure 6 Stress-strain curves of perovskite films without passivation layer, with only passivation molecules, with only oxide nanocrystals, and with a mixture of both.

[0024] Figure 7 Current density-voltage curves of small-area perovskite solar cells prepared with and without bottom nanocrystal hybrid passivation method.

[0025] Figure 8 Current density-voltage curves of large-area perovskite solar modules prepared using the bottom nanocrystal hybrid passivation method. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0028] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0029] Comparative Example 1 This embodiment adopts the scraping method to prepare the perovskite solar cell, and the specific preparation process is as follows: 1. Prepare a monolayer of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACZ) as a hole transport layer on a cleaned ITO substrate, about 20 nm.

[0030] 2. Preparation of Cs with a thickness of about 800 nm by air-blowing blade coating 0.05 FA 0.95 PbI3 perovskite light absorbing layer.

[0031] 3. Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as the electron transport layer with a thickness of about 20 nm.

[0032] 4. Finally, a layer of Cu with a thickness of 150 nm is deposited by thermal evaporation as the back metal electrode.

[0033] Comparative Example 2 This embodiment adopts the scraping method to prepare the perovskite solar cell with the bottom passivation layer. The specific preparation process is as follows: 1. Prepare a monolayer of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACZ) as a hole transport layer on a cleaned ITO substrate, about 20 nm.

[0034] 2. Prepare a bottom passivation layer on the prepared hole transport layer by using a doctor blade method. Dissolve the passivation molecule 4-fluorophenethylammonium chloride (4F-PEACl) in the solvent ethanol (EA) to prepare a solution with a concentration of 1 mg / mL, then use a nitrogen gas blowing volume of about 30 psi and a doctor blade speed of about 20 mm / s to prepare the bottom passivation layer, and anneal at 100 °C for 2 min.

[0035] 3. Preparation of Cs with a thickness of about 800 nm by air-blowing coating 0.05 FA0.95 PbI3 perovskite light absorbing layer.

[0036] 4. Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as the electron transport layer with a thickness of about 20 nm.

[0037] 5. Finally, a layer of Cu with a thickness of 150 nm is deposited by thermal evaporation as the back metal electrode.

[0038] Comparative Example 3 This embodiment adopts the scraping method to prepare the perovskite solar cell with the bottom nanocrystalline passivation layer. The specific preparation process is as follows: 1. Prepare a monolayer of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACZ) as a hole transport layer on a cleaned ITO substrate, about 20 nm.

[0039] 2. Prepare a bottom passivation layer on the prepared hole transport layer by using a doctor blade method. Dissolve nanosilicon dioxide in solvent ethanol (EA) to prepare a solution with a concentration of 1 mg / mL, then use a nitrogen gas blowing volume of about 30 psi and a doctor blade speed of about 20 mm / s to prepare the bottom passivation layer, and anneal at 100 °C for 2 min.

[0040] 3. Preparation of Cs with a thickness of about 800 nm by air-blowing coating 0.05 FA 0.95 PbI3 perovskite light absorbing layer.

[0041] 4. Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as the electron transport layer with a thickness of about 20 nm.

[0042] 5. Finally, a layer of Cu with a thickness of 150 nm is deposited by thermal evaporation as the back metal electrode. Example 1

[0043] In this example, a perovskite solar cell (effective area 0.049 cm) with a bottom nanocrystalline mixed passivation layer was prepared by a scraping method. 2 ), the specific preparation process is as follows: 1. Prepare a monolayer of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACZ) as a hole transport layer on a cleaned ITO substrate, about 20 nm.

[0044] 2. Prepare the bottom nanocrystalline hybrid passivation layer on the prepared hole transport layer by scraping. Mix and dissolve nanosilicon dioxide and passivation molecule 4-fluorophenethylammonium chloride (4F-PEACl) in ethanol (EA) at a mass ratio of 1:1 to prepare a solution with a concentration of 1 mg / mL. Then, use a nitrogen gas blowing volume of about 30 psi and a scraper speed of about 20 mm / s to prepare the bottom nanocrystalline hybrid passivation layer, and anneal at 100 °C for 2 min.

[0045] 3. Preparation of Cs with a thickness of about 800 nm by air-blowing coating 0.05 FA 0.95 PbI3 perovskite light absorbing layer.

[0046] 4. Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as the electron transport layer with a thickness of about 20 nm.

[0047] 5. Finally, a layer of Cu with a thickness of 150 nm is deposited by thermal evaporation as the back metal electrode.

[0048] The perovskite films prepared under the conditions of Comparative Example 1 and Example 1 were tested. Figure 2 It can be seen that the introduction of nanocrystal mixed passivation molecules can make more organic passivation molecules remain at the bottom interface; Figure 3 It can be seen that the peak shift at different incident angles is weakened after the bottom nanocrystal hybrid passivation, indicating that the longitudinal tensile stress of the perovskite layer is relieved.

[0049] The passivation layers prepared under the conditions of Comparative Example 2, Comparative Example 3 and Example 1 were tested. Figure 4 It can be seen that the surface of oxide nanocrystals is rich in -OH, which forms hydrogen bonds with passivating molecules, causing the -OH bond vibration to move to a lower wave number, indicating the strong bond and interaction between the nanocrystals and the passivating molecules.

[0050] The perovskite films prepared under the conditions of Comparative Examples 1-3 and Example 1 were tested. Figure 5 It can be seen that introducing nanocrystal mixed passivation at the bottom can further reduce the defects of perovskite.

[0051] The perovskite films prepared under the conditions of Comparative Examples 1-3 and Example 1 were tested. Figure 6 It can be seen that the introduction of nanocrystal hybrid passivation at the bottom can greatly improve the interfacial adhesion.

[0052] The titanium ore solar cells prepared in Comparative Example 1 and Example 1 were tested. Figure 7 It can be seen that the photoelectric conversion efficiency of solar cells with the introduction of nanocrystal mixed passivation at the bottom is increased from 23.02% to 25.48%. Example 2

[0053] In this example, a large-area perovskite solar cell module (effective area 20.25 cm) with a bottom nanocrystalline mixed passivation layer was prepared by a scraping method. 2 ), the specific preparation process is as follows: 1. Laser edge cleaning and cutting of p1 were performed on the cleaned ITO substrate, and then a monolayer of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACZ) was prepared on it as a hole transport layer, about 20 nm.

[0054] 2. Prepare the bottom nanocrystalline hybrid passivation layer on the prepared hole transport layer by scraping. Mix and dissolve nanosilicon dioxide and passivation molecule 4-fluorophenethylammonium chloride (4F-PEACl) in ethanol (EA) at a mass ratio of 1:1 to prepare a solution with a concentration of 1 mg / ml. Then, use a nitrogen gas blowing volume of about 30 psi and a scraper speed of about 20 mm / s to prepare the bottom nanocrystalline hybrid passivation layer, and anneal at 100 °C for 2 min.

[0055] 3. Preparation of Cs with a thickness of about 800 nm by air-blowing coating 0.05 FA 0.95 PbI3 perovskite light absorbing layer.

[0056] 4. Preparation of a layer of fullerene (C) by thermal evaporation 60 ) as the electron transport layer with a thickness of about 20 nm.

[0057] 5. Cut p2 using laser.

[0058] 6. Use thermal evaporation to deposit a 180 nm thick Cu layer as the back metal electrode.

[0059] 7. Finally, use laser to cut p3.

[0060] The titanium ore solar cell of Example 2 was tested. Figure 8 It can be seen that the solar cell with the introduction of nanocrystal hybrid passivation at the bottom achieved a photoelectric conversion efficiency of 20.28% on an effective area of ​​20.25 cm².

Claims

1. A perovskite solar cell, characterized in that: From the light-receiving front side to the light-receiving back side, it includes: a transparent conductive substrate, a hole transport layer, a nanocrystalline mixed passivation layer, a perovskite light-absorbing layer, an electron transport layer and a back electrode; The nanocrystalline mixed passivation layer is made of insulating oxide and organic passivation molecules, and the mass ratio of the insulating oxide to the organic passivation molecules is 3:1-1:

3.

2. The perovskite solar cell according to claim 1, characterized in that The insulating oxide is silicon oxide, aluminum oxide or zirconium oxide, and the particle size of the insulating oxide is 5-100 nm.

3. The perovskite solar cell according to claim 2, characterized in that: The organic passivation molecule is PEAI, 4F-PEAI, 4F-PEACl, PEACl, CF3-PACl, EDADI, TOPO, ODT or PPh3.

4. The perovskite solar cell according to claim 1, characterized in that: The transparent conductive substrate is an indium tin oxide substrate, an indium tungsten oxide substrate, a fluorine-doped tin oxide substrate, an indium zinc oxide substrate or an aluminum-doped zinc oxide substrate.

5. The perovskite solar cell according to claim 1, characterized in that: The hole transport layer is made of p-type semiconductor material.

6. The perovskite solar cell according to claim 1, characterized in that: The perovskite light-absorbing layer is made of perovskite material ABX3, wherein: A is selected from formamidine ion, methylamine ion, cesium ion; B is selected from lead ion, tin ion, germanium ion; X is selected from iodine ion, bromide ion, chloride ion.

7. The perovskite solar cell according to claim 1, characterized in that: The electron transport layer is made of n-type semiconductor material.

8. The method for preparing a passivated perovskite solar cell according to any one of claims 1 to 7, characterized in that: The following steps are involved: providing a transparent conductive substrate; forming a hole transport layer on the upper surface of the transparent conductive substrate; forming a nanocrystalline hybrid passivation layer on the upper surface of the hole transport layer; forming a perovskite light absorbing layer on the upper surface of the bottom nanocrystalline hybrid passivation layer; forming an electron transport layer on the upper surface of the perovskite light absorbing layer; A back electrode is formed on the upper surface of the electron transport layer.

9. The preparation method according to claim 8, characterized in that: The nanocrystalline mixed passivation layer is formed on the upper surface of the hole transport layer by dissolving the insulating oxide and the organic passivation molecules in a solvent and then coating them on the hole transport layer by a scraping method.

10. A photovoltaic module, characterized in that: include: At least one cell string, the cell string comprising at least two perovskite solar cells according to claim 1.

Citation Information

Patent Citations

  • Perovskite solar cell taking zirconium oxide passivated tin oxide as electron transport layer and method

    CN111477747A

  • Perovskite solar cell

    CN112582543A

  • Perovskite solar cell and preparation method thereof

    CN116261338A

  • Perovskite solar cell with passivation structure and preparation method thereof

    CN116322091A

  • Perovskite solar cell and preparation method thereof

    CN118870841A

Cited By

  • Perovskite solar cell with modified hole transport layer and preparation method of perovskite solar cell

    CN120112059A